Digital Narratives of Makassar Women Entrepreneurs: Negotiating Local Values and Market Visibility in the Era of Social Commerce - Riu, Isma Azis (Malaqbi Publisher, 2025)
This qualitative study investigates how women entrepreneurs in Makassar navigate the moral economy of digital visibility by integrating siri'-the local ethic of dignity and honor—into their social commerce practices. Using a narrative-phenomenological approach, data were collected from 20 women entrepreneurs across fashion, food, and craft sectors through life-history interviews, digital ethnography, and participatory diaries. The analysis identifies five interrelated narrative themes: service visibility (framing exposure as accountability), modest aesthetics (curating self-presentation aligned with cultural modesty), family honor framing (redefining profit as collective achievement), strategic disclosure (balancing marketing needs with moral caution), and community surveillance and support (negotiating judgment and solidarity). Findings reveal that siri’ functions as a cultural compass guiding women’s digital storytelling, enabling ethically calibrated visibility that blends moral restraint with entrepreneurial aspiration. Digital platforms become arenas of moral negotiation where reputation, family pride, and market success intersect. The study contributes to a humanistic understanding of digital marketing as culturally embedded moral work rather than mere self-promotion. It calls for culturally sensitive digital literacy programs and platform designs that allow selective visibility and community-based trust-building mechanisms, affirming that sustainable digital entrepreneurship in Makassar depends as much on ethical coherence as on technical competence.